2019
DOI: 10.3168/jds.2018-15312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium salicylate on glucose kinetics and insulin signaling in postpartum dairy cows

Abstract: Low-grade inflammation has been implicated as a contributor to metabolic disease during the transition to lactation. In previous work, administration of sodium salicylate (SS) for 7 d led to hypoglycemia in mature dairy cows in early lactation. The purpose of this study was to identify the mode of action underlying this response to SS. Twenty mature (parity 3) cows were assigned alternately at time of calving to either control or SS treatments; the control received a molasses placebo in drinking water, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…We subsequently conducted a follow-up study where multiparous cows were treated with oral sodium salicylate, and plasma glucose turnover was determined with a stable isotope dilution method on day 7 of lactation. We found that glucose turner rate was decreased by 25%, despite a significant decrease in insulinglucagon ratio (Montgomery et al, 2019). Given the steadystate assumptions used in metabolic flux studies, the decline in glucose turnover reflected both a decreased use of glucose and a decreased supply.…”
Section: Implications Of Non-steroidal Anti-inflammatory Therapy On Dmentioning
confidence: 71%
“…We subsequently conducted a follow-up study where multiparous cows were treated with oral sodium salicylate, and plasma glucose turnover was determined with a stable isotope dilution method on day 7 of lactation. We found that glucose turner rate was decreased by 25%, despite a significant decrease in insulinglucagon ratio (Montgomery et al, 2019). Given the steadystate assumptions used in metabolic flux studies, the decline in glucose turnover reflected both a decreased use of glucose and a decreased supply.…”
Section: Implications Of Non-steroidal Anti-inflammatory Therapy On Dmentioning
confidence: 71%
“…Other studies involving NSAID in the postpartum period appeared to improve liver function, with reductions in plasma AST and GLDH 29 . Moreover, oral anti-inflammatory medication in the first week postpartum resulted in greater hepatic insulin sensitivity 32,67,68 . Other early postpartum studies with NSAID have been performed, but the metabolic effects are not consistent 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cows treated with oral meloxicam produced more milk in early lactation, had reduced odds of subclinical mastitis, and reduced odds of early lactation culling 31 . In a recent study, Montgomery et al 32 explored the mechanistic role of inflammatory signaling in glucose and energy metabolism of dairy cows treated with sodium salicylate in drinking water in the first week postpartum. Although treated mature transition cows tended to suppress whole-body glucose turnover, no major differences were found in markers of SI and energy metabolism.…”
mentioning
confidence: 99%
“…A growing body of evidence suggests that inflammation is involved in p.p. IR, and inflammation-dependent IR is thought to be an adaptive response of homeorhetic adaptation in early lactation (Farney et al, 2013;Montgomery et al, 2019).…”
Section: Partitioning and Mobilizationmentioning
confidence: 99%